(untitled) (Shiksha Shastra Saurabh, 2025)
The study explores how cognitive biases affect the aspect of retail investor’s herding behavior in the context of Nepalese market. This study is based upon the theoretical aspect of Prospect theory and Behavioral theory. Perfect theory explains how investors strengthen herding behavior are tending losses more fatly than equal profits. Behavior Finance theory explains systematic departure from rationality. In terms of theoretical aspect for connecting psychological biases to collect market behavior is succeeding by these frameworks. The study was taken from 250 active retail investors from Nepal stock exchange (NEPSE) which emphasis the qualitative approach with cross sectional research design along with structured questionnaire. The analysis was approved with the 5-point Likert scale through different data gathered together for the analysis with different statistical tools like regression models, PCA, correlation, ANOVA and reliability test. The findings show that whereas loss aversion and regret aversion mainly affect choices through herding behavior and overconfidence which has both direct and indirect effects on the investment decisions. The explanatory significance of behavior variables in developing countries was highlighted by regression models, which accounted for around half of the variance in investment decision making. By confirming a mediation model in the Nepalese setting and showing that herding behavior increases the impact of cognitive biases on investment results, this study adds to the body on behavioral finance. The results have consequences for policy actions meant to improve market stability, regulatory supervision, regulatory supervision and investor education.